Poor supply chain management and stock-outs of point-of-care diagnostic tests in Upper East Region’s primary healthcare clinics, Ghana - Kuupiel, Desmond; Tlou, Boikhutso; Bawontuo, Vitalis; Drain, Paul K.; Mashamba-Thompson, Tivani P. (PloS one, 2019)
Several supply chain components are important to sustain point-of-care (POC) testing services in rural settings. To evaluate the availability of POC diagnostic tests in rural Ghana's primary healthcare (PHC) clinics, we conducted an audit of the supply chain management for POC diagnostic services in rural Upper East Region's (UER) PHC clinics, Ghana to determine the reasons/causes of POC tests deficiencies. We conducted a review of accessible POC diagnostics in 100 PHC clinics in UER, Ghana from February to March 2018. We used a monitoring audit tool adopted from the World Health Organization and Management Science for Health guidelines for supply chain management of diagnostics for compliance. We determined a clinic's compliance with the stipulated guidelines, and a composite compliant score was defined as a percentage rating of 90 to 100%. We used univariate logistic regression analysis in Stata 14 to determine the level of association between supply chain management and the audit variables. Overall, the composite compliant score of supply chain management for existing POC tests was at 81% (95%CI: 79%-82%). The mean compliance with distribution guidelines was at 93.8% (95%CI: 91.9%-95.6%) the highest score, whilst inventory management scored the lowest, at 53.5% (95%CI: 49.5%-57.5%) compliance. Of the 13 districts in the region, the results showed complete stock-out of blood glucose test in all selected PHC clinics in seven (53.8%) districts, haemoglobin and hepatitis B virus test in three (23.1%), and urine protein test in two (15.4%) districts. Based on our univariate logistics regression models, stock-out of tests at the Regional Medical and District Health Directorates stores in the region, high clinic attendance, lack of documentation of expiry date/expired tests, poor documentation of inventory level, poor monitoring of monthly consumption level, and failure to document unexplained losses of the various POC tests were significant predictors of complete test stock-out in most of the clinics in the Upper East Region. There is poor supply chain management of POC diagnostic tests in UER's PHC clinics. Improvement in inventory management and human resource capacity for POC testing is critical to ensure accessibility and sustainability of POC diagnostic services in resource-limited settings PHC clinics.